Pickleball is life : the complete guide to feeding your obsession - McHugh, Erin, 1952- (Harvest, an imprint of William Morrow, 2022)
"The fastest-growing sport in America is also the most fun, friendly, inclusive, and easy-to-learn pastime since ... well, ever! Pickleball Is Life celebrates the weird and wonderful world of this runaway sensation, covering the sport's quirky origins, its modern-day cult following, and everything in between." --